Fostering students' epistemic agency through the co‐configuration of moth research. Issue 6 (24th July 2018) - Stroupe, David; Caballero, Marcos D.; White, Peter
Abstract: We argue that students should take on roles as epistemic agents —those who shape knowledge production and practices of a community. In this study, the research team—a science educator and two scientists—worked with a sixth‐grade teacher to provide 90 students with opportunities to take up epistemic agency over a 22‐day unit about moth ecology. We used cultural historical activity theory (CHAT) to analyze the co‐configuration of activity. During planning, tensions arose among the research team around how and why to position students as epistemic agents, while still attending to meaningful science questions. During instruction, students prompted the constant negotiation of epistemic roles and practices as they acted on shifting agentic participation structures.